Egg development, hatching, and larval development of Marble Goby Oxyeleotris marmoratus under artificial rearing conditions - Senoo, Shigeharu; Kaneko, Masaharu; Cheah, Sin Hock; Ang, Kok Jee (Springer, 1994)
To establish a seed production technique for marble goby Oxyeleotris marmoratus the eggs and larvae were observed under artificial rearing conditions. Newly ovulated eggs from a female of 255 g in body weight were measured 0.94 and 0.62mm in the long and short axes, and weighed 1,669.6 eggs/g. After fertilization, the egg had a bundle of adhesive filaments at the basal end of the egg membrane and was elongated after 1 h, when it measured 2.3 and 0.63 mm in its long and short axes, respectively. The eggs hatched during 41--150h after fertilization (AF) at 27.2--27.5°C. Early and late hatching resulted in high mortality. The optimum hatching stage was considered just before and after the embryonic eyes had become slightly pigmented. All embryonic heads were located at the basal part of the egg and this was taken as normal egg development for O. marmoratus. In spite of their well-developed eyes and mouths, and the fact that they exhibited the active S-posture, the larvae did not feed on artificial powdered feed or Brachionus spp. for 4--6 days (d) AF, and the mortality before the feeding of Brachionus spp. was much higher than that of the later stages. They shifted their habitat from pelagic to benthic from 30 d AF. About 1,600 seeds (mean total length, 28.5 mm) were produced from 16,000 hatched larvae (mean total length, 3.54 mm) at 70 d AF.